Pharmacological, antioxidant, genotoxic studies and modulation of rat splenocyte functions by Cyperus rotundus extracts - Soumaya, Kilani-Jaziri (BioMed Central, 2013)
BACKGROUND: Cyperus rotundus Linn. (Cyperaceae) is a Tunisian medicinal plant used in folkloric (traditional) medicine to treat stomach disorders and inflammatory diseases. The present study explored the analgesic, anti-inflammatory and genotoxic activities of extracts from the aerial parts of C. rotundus. The antioxidant capacity and the modulation of splenocyte functions by these extracts were also investigated in mice. The phytochemical analysis was carried out using standard methods. METHODS: Aqueous, ethyl acetate, methanol and TOF-enriched extracts (300, 150, and 50 μg/ml) were evaluated for their analgesic and anti-inflammatory activities. 4, 2, and 1 mg/ml of each extract were tested to investigate their effect on lipid peroxidation. The genotoxic study was monitored by measuring the structural chromosome aberrations of mice treated with 300 mg/kg of extract. The proliferation of lymphocytes in the absence and presence of mitogens was assessed at a concentration range 1–1000 μg/ml. RESULTS: The tested extracts were able to decrease the mouse ear oedema induced by xylene. Furthermore, it was shown that the same extracts reduced the number of abdominal contractions caused by acetic acid in mice, revealing the peripheral analgesic activity of these extracts. It is worth noting that mice treated with doses up to 300 mg/kg b.w. of Cyperus rotundus extracts did not exhibit any toxicity. The tested extracts significantly enhance lymphocyte proliferation at 1 mg/ml. CONCLUSIONS: It appears that C. rotundus extracts contain potent components such as flavonoids that may potentially be useful for modulating the immune cell functions, provoking analgesic, anti-inflammatory and antioxidant effects.